An Intemporal Model of Asset Prices in a Markov Economy with a Limiting Stationary Distribution - Kazemi, Hossein B. (Review of Financial Studies, 1992)
A testable single-beta model of asset prices is presented. If state variables have a long-run stationary joint density function, then the rate return on a very long-term default-free discount bond will be perfectly correlated with the representative investor’s marginal utility of consumption. Thus, the covariance of an asset’s return with the return on such a bond will be an appropriate measure of the asset’s riskiness. The model can be, therefore, applied or tested even though the market portfolio or aggregate consumption may not be observable. It also is shown that the expected rate of return on a very long-term bond is equal to its variance. This proposition can be tested to determine whether state variables follow stationary processes.